Wrinkly-Spreader Fitness in the Two-Dimensional Agar Plate Microcosm: Maladaptation, Compensation and Ecological Success - Spiers, Andrew J. (Public Library of Science, 2007)
Bacterial adaptation to new environments often leads to the establishment of new genotypes with significantly altered phenotypes. In the Wrinkly Spreader (WS), ecological success in static liquid microcosms was through the rapid colonisation of the air-liquid interface by the production of a cellulose-based biofilm. Rapid surface spreading was also seen on agar plates, but in this two-dimensional environment the WS appears maladapted and rapidly reverts to the ancestral smooth (SM)-like colony genotype. In this work, the fitness of WS relative to SM in mixed colonies was found to be low, confirming the WS instability on agar plates. By examining defined WS mutants, the maladaptive characteristic was found to be the expression of cellulose. SM-like revertants had a higher growth rate than WS and no longer expressed significant amounts of cellulose, further confirming that the expression of this high-cost polymer was the basis of maladaptation and the target of compensatory mutation in developing colonies. However, examination of the fate of WS-founded populations in either multiple-colony or single mega-colony agar plate microcosms demonstrated that the loss of WS lineages could be reduced under conditions in which the rapid spreading colony phenotype could dominate nutrient and oxygen access more effectively than competing SM/SM-like genotypes. WS-like isolates recovered from such populations showed increased WS phenotype stability as well as changes in the degree of colony spreading, confirming that the WS was adapting to the two-dimensional agar plate microcosm.